Modified fiberglass tire and preparation method thereof, composition for asphalt shingles, asphalt shingles and preparation method and application thereof

By using graphene oxide and polyphosphate modified glass fiber tires and modified asphalt materials in asphalt shingles, the problem of insufficient tear resistance and electromagnetic shielding performance of asphalt shingles is solved, and high-performance asphalt shingles are achieved , suitable for the waterproof and electromagnetic shielding requirements of building exterior walls.

CN118185126BActive Publication Date: 2024-12-20DEZHOU KESHUN BUILDING MATERIALS CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410349824.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2024-12-20
Estimated Expiration
2044-03-26

AI Technical Summary

Technical Problem

The existing asphalt shingles have low tear resistance and poor electromagnetic shielding performance. Traditional electromagnetic shielding materials lack sufficient shielding ability to low-frequency magnetic field, and the content of contaminated metal powder may lead to environmental pollution.

Method used

The aqueous solution containing graphene oxide and polyphosphate is heated with the raw material glass fiber tire to prepare the modified glass fiber tire and combine it with the modified asphalt material to form asphalt shingles with a dense three-dimensional network structure to improve its electromagnetic shielding and Tear resistance.

Benefits of technology

The produced asphalt shingles have excellent tear resistance (tear strength > 35N) and excellent electromagnetic shielding performance (electromagnetic shielding performance > 35dB), and are suitable for strict building exterior wall waterproofing and electromagnetic shielding applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118185126B_ABST
    Figure CN118185126B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of asphalt shingles, and discloses a modified glass fiber tire and a preparation method thereof, a composition for asphalt shingles, an asphalt shingle and a preparation method and application thereof. The method for preparing the modified glass fiber tire comprises: heating an aqueous solution I containing graphene oxide and polyphosphate, a raw glass fiber tire and a reducing agent to obtain a modified glass fiber tire. The method for preparing the modified glass fiber tire provided by the present invention is simple and highly operable. The prepared modified glass fiber tire has a dense three-dimensional network structure, can be applied to the field of asphalt shingles, and thus improves the electromagnetic shielding performance of the asphalt shingles. The asphalt shingles prepared by using the composition for asphalt shingles provided by the present invention have excellent tear resistance and excellent electromagnetic shielding performance, and are particularly suitable for the field of building exterior walls with strict requirements on waterproofing and electromagnetic shielding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of asphalt shingles, and in particular to a modified glass fiber tire and a preparation method thereof, a composition for asphalt shingles, an asphalt shingle and a preparation method and application thereof. Background Art

[0002] At present, the electromagnetic shielding materials for exterior walls are generally made by adding carbon black, graphite, metal powder, conductive fiber, etc. However, carbon black and graphite are only more prominent in conductivity, and their shielding ability for low-frequency magnetic fields is poor. In addition, the types of electromagnetic shielding materials added are relatively single, and the overall shielding effectiveness is poor. Metal powder (such as lead) pollutes the environment, and adding it to exterior wall materials may cause metal corrosion problems. Asphalt shingles are commonly used waterproof materials for building roofs, and are often used to tightly cover the exterior surface of buildings. This application method is consistent with the "wrapping" conditions required for electromagnetic shielding, so asphalt shingles are suitable for use as electromagnetic shielding materials.

[0003] CN206220376U discloses a conductive snow-melting colored asphalt shingle, the shingle body is a composite of a multi-layered structure. The structural layers are arranged in the order of colored gravel layer, upper conductive modified asphalt layer, carcass layer, lower modified asphalt self-adhesive layer, and isolation film layer from the upper surface to the lower surface, wherein the upper conductive modified asphalt layer and the lower conductive modified asphalt layer are made by adding graphite powder to polymer modified asphalt at an amount of 30%, so that the layer has a resistance function and can be heated and heated under external power to quickly melt snow and ice. However, the amount of graphite powder added in this scheme is large, and the cost is high; and the graphite powder is difficult to disperse effectively, and the electromagnetic shielding performance of the obtained asphalt shingle is poor. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low tearing strength and poor electromagnetic shielding performance of existing asphalt shingles.

[0005] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a modified glass fiber mat, the method comprising the following steps:

[0006] The aqueous solution I containing graphene oxide and polyphosphate, the raw glass fiber tire and the reducing agent are heated to obtain a modified glass fiber tire;

[0007] The concentration of graphene oxide in the aqueous solution I is 30-80 mg / mL, and the concentration of polyphosphate is 1-3 mg / mL;

[0008] The raw material glass fiber tire has a gram weight of ≥250g / m 2 ;

[0009] Relative to every 1m 2The raw glass fiber tire, the amount of the graphene oxide is 10-50g, and the amount of the reducing agent is 15-75mL.

[0010] The second aspect of the present invention provides a modified glass fiber mat prepared by the method described in the first aspect.

[0011] A third aspect of the present invention provides a composition for asphalt shingles, the composition comprising a modified glass fiber mat and a modified asphalt material;

[0012] Relative to every 1m 2 The modified glass fiber tire, the content of the modified asphalt material is 1000-2000g;

[0013] Based on the total weight of the modified asphalt material, the modified asphalt material contains 75wt%-85wt% of base asphalt, 3wt%-8wt% of polyolefin wax powder, 3wt%-8wt% of thermoplastic elastomer and 5wt%-15wt% of filler;

[0014] The modified glass fiber tire is the modified glass fiber tire described in the second aspect above.

[0015] The fourth aspect of the present invention provides a method for preparing an asphalt shingle, the method using the components of the composition described in the third aspect, comprising:

[0016] (1) mixing base asphalt, polyolefin wax powder, thermoplastic elastomer and filler to obtain modified asphalt material;

[0017] (2) The modified glass fiber base is impregnated with the modified asphalt material to obtain the asphalt shingle.

[0018] The fifth aspect of the present invention provides an asphalt shingle prepared by the method described in the fourth aspect.

[0019] The sixth aspect of the present invention provides the use of the asphalt shingle described in the fifth aspect in waterproof materials.

[0020] The method for preparing the modified glass fiber tire provided by the present invention is simple, highly operable, economical and environmentally friendly. The prepared modified glass fiber tire has a dense three-dimensional network structure and can be applied to the field of asphalt shingles, thereby improving the electromagnetic shielding performance and tear resistance of the asphalt shingles.

[0021] The asphalt shingles prepared by the asphalt shingle composition provided by the present invention have excellent tear resistance (tear strength>35N) and excellent electromagnetic shielding performance (electromagnetic shielding performance>35dB), and are particularly suitable for the field of building exterior walls with strict requirements on waterproofing and electromagnetic shielding. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1is a scanning electron microscope image of the glass fiber mat I used in Preparation Example C1 of the present invention;

[0023] Figure 2 It is a scanning electron microscope image of the modified glass fiber tire prepared in Preparation Example C1 of the present invention. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] As mentioned above, the first aspect of the present invention provides a method for preparing a modified glass fiber mat, the method comprising the following steps:

[0026] The aqueous solution I containing graphene oxide and polyphosphate, the raw glass fiber tire and the reducing agent are heated to obtain a modified glass fiber tire;

[0027] The concentration of graphene oxide in the aqueous solution I is 30-80 mg / mL, and the concentration of polyphosphate is 1-3 mg / mL;

[0028] The raw material glass fiber tire has a gram weight of ≥250g / m 2 ;

[0029] Relative to every 1m 2 The raw glass fiber tire, the amount of the graphene oxide is 10-50g, and the amount of the reducing agent is 15-75mL.

[0030] In the present invention, the thickness of the raw glass fiber tire is 1.2-2.5 mm.

[0031] Preferably, the aqueous solution I is prepared by stirring and mixing a graphene oxide aqueous dispersion and polyphosphate. The graphene oxide can be commercially available or homemade.

[0032] Preferably, the amount of the graphene oxide aqueous dispersion and the polyphosphate is controlled so that the concentration of graphene oxide in the aqueous solution I is 30-80 mg / mL, and the concentration of polyphosphate is 1-3 mg / mL. The inventors of the present invention have found that the use of aqueous solution I (the concentration of graphene oxide is 30-80 mg / mL, and the concentration of polyphosphate is 1-3 mg / mL) is more conducive to modifying the raw glass fiber tire.

[0033] Preferably, the concentration of graphene oxide in the graphene oxide aqueous dispersion is 30-80 mg / mL.

[0034] The present invention has no special requirements on the stirring and mixing conditions, as long as the graphene oxide dispersion and the polyphosphate can be mixed uniformly.

[0035] According to a preferred embodiment, the graphene oxide is prepared by a method comprising the following steps:

[0036] S1: contacting and mixing graphite, potassium nitrate, sulfuric acid and potassium permanganate to obtain intermediate I;

[0037] The concentration of the sulfuric acid is 90wt%-98wt%;

[0038] S2: in the presence of water, stirring the intermediate I and hydrogen peroxide to obtain the graphene oxide;

[0039] The concentration of the hydrogen peroxide is 25-30 wt %.

[0040] Preferably, in step S1, the weight ratio of the graphite to the potassium permanganate is 1:0.8-1.2.

[0041] Preferably, in step S1, the specific operation of contact mixing includes:

[0042] S11: performing a first stirring reaction on sulfuric acid, graphite and potassium nitrate to obtain a mixture I;

[0043] S12: subjecting potassium permanganate to a second stirring reaction with the mixture I to obtain an intermediate I.

[0044] Preferably, in step S11, the weight ratio of the graphite to the potassium nitrate is 1:0.8-1.2.

[0045] Preferably, in step S11, the conditions of the first stirring reaction include: a rotation speed of 100-300 rpm, a temperature of 0-5°C, and a time of 0.5-2h.

[0046] Preferably, in step S11, the amount of sulfuric acid used is 180-220 mL relative to 10 g of graphite.

[0047] Preferably, in step S12, the conditions of the second stirring reaction include: a rotation speed of 300-400 rpm, a temperature of 30-50° C., and a time of 20-40 min.

[0048] Preferably, in step S2, the volume ratio of the water to the hydrogen peroxide is 1:0.2-0.3.

[0049] Preferably, relative to 1 g of potassium permanganate, the volume usage of the hydrogen peroxide is 8-12 mL.

[0050] Preferably, in step S2, the stirring reaction conditions include: a rotation speed of 300-400 rpm, a temperature of 90-100° C., and a time of 0.5-1.5 h.

[0051] It should be noted that the present invention may also involve post-treatment known in the art after the stirring reaction, for example: filtering, first washing, centrifuging, second washing, and first drying the product after the stirring reaction in sequence. The present invention has no special requirements for the first washing method. For example, the present invention uses hydrochloric acid with a concentration of 1-2 mol / L for the first washing; the present invention has no special requirements for the second washing method, as long as the pH of the solution after the water washing is 6.8-7.2; the present invention has no special requirements for the first drying method, as long as the product after the second washing can be completely dried.

[0052] Preferably, the conditions of the heating treatment include: temperature of 80-120° C. and time of 1-3 h.

[0053] It should be noted that the present invention may also involve post-treatment known in the art after the heating treatment, for example, drying the product after the heating treatment. The present invention has no special requirements for the drying method, as long as the material is completely dried.

[0054] Preferably, the polyphosphate is at least one of ammonium polyphosphate, sodium tripolyphosphate, potassium tripolyphosphate, sodium polyphosphate and sodium hexametaphosphate.

[0055] Preferably, the reducing agent is hydrazine hydrate and / or vitamin C. More preferably, it is hydrazine hydrate.

[0056] The present invention has no special requirements on the type of water, which may be deionized water, ultrapure water, etc., and those skilled in the art can select it according to needs.

[0057] As mentioned above, the second aspect of the present invention provides a modified glass fiber mat prepared by the method described in the first aspect.

[0058] As mentioned above, the third aspect of the present invention provides a composition for asphalt shingles, the composition comprising a modified glass fiber mat and a modified asphalt material;

[0059] Relative to every 1m 2 The modified glass fiber tire, the content of the modified asphalt material is 1000-2000g;

[0060] Based on the total weight of the modified asphalt material, the modified asphalt material contains 75wt%-85wt% of base asphalt, 3wt%-8wt% of polyolefin wax powder, 3wt%-8wt% of thermoplastic elastomer and 5wt%-15wt% of filler;

[0061] The modified glass fiber tire is the modified glass fiber tire described in the second aspect above.

[0062] Preferably, the base asphalt has a needle penetration of 65-95 0.1 mm at 25°C and a softening point of 40-70°C.

[0063] Preferably, the viscosity of the polyolefin wax powder at 130° C. is 100-500 mPa.s, the softening point is 100-120° C., and the number average molecular weight is 1200-3000. The inventors found that under this preferred condition, the tearing performance and electromagnetic shielding performance of the prepared asphalt shingles are better.

[0064] Preferably, the base asphalt is selected from at least one of 70# asphalt, 90# asphalt and 200# asphalt.

[0065] Preferably, the thermoplastic elastomer is a butadiene-styrene-butadiene triblock copolymer and / or a butadiene-isoprene-butadiene triblock copolymer. The inventors have found that in this preferred embodiment, the tearing performance of the prepared asphalt shingles is higher.

[0066] Preferably, the thermoplastic elastomer is a butadiene-styrene-butadiene triblock copolymer.

[0067] Preferably, the polyolefin wax powder is selected from at least one of oxidized polyethylene wax, polyethylene wax and polypropylene wax.

[0068] Preferably, the filler is selected from at least one of talc, heavy calcium carbonate, montmorillonite, kaolin and metakaolin; and the average particle size of the filler is 13-75 μm.

[0069] More preferably, the filler is heavy calcium.

[0070] As mentioned above, the fourth aspect of the present invention provides a method for preparing asphalt shingles, which is carried out using the components in the composition described in the third aspect, comprising:

[0071] (1) mixing base asphalt, polyolefin wax powder, thermoplastic elastomer and filler to obtain modified asphalt material;

[0072] (2) The modified glass fiber base is impregnated with the modified asphalt material to obtain the asphalt shingle.

[0073] Preferably, in step (1), the first mixing conditions include: a rotation speed of 100-300 rpm, a temperature of 160-200° C., and a time of 1-3 h.

[0074] Preferably, in step (2), the conditions of the infiltration treatment include: a temperature of 180-220° C. and a time of 0.5-5 min.

[0075] As mentioned above, the fifth aspect of the present invention provides an asphalt shingle prepared by the method described in the fourth aspect.

[0076] As mentioned above, the sixth aspect of the present invention provides the use of the asphalt shingle described in the fifth aspect in waterproof materials.

[0077] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the instruments, reagents, materials, etc. involved are all conventional instruments, reagents, materials, etc., which can be obtained through regular commercial channels. Among them, unless otherwise specified, the reagents used are all commercially available analytically pure products.

[0078] Graphite: purchased from Anergy, CAS: 7782-42-5, 99.9%.

[0079] Sulfuric acid: concentration is 98wt%.

[0080] Hydrogen peroxide: concentration is 30wt%.

[0081] Hydrochloric acid: concentration is 1 mol / L.

[0082] Graphene: purity 97%, purchased from Shanghai Yien Chemical Technology Co., Ltd.

[0083] Graphene oxide:

[0084] Graphene oxide I: Homemade.

[0085] Graphene oxide II: purchased from Darley Company, model is graphene oxide powder Darl-1.

[0086] Polyphosphate:

[0087] Sodium tripolyphosphate: purchased from Anage Company, CAS: 7758-29-4.

[0088] Sodium carbonate: purchased from Anage Company, CAS number: 497-19-8.

[0089] Raw material glass fiber tire:

[0090] Glass fiber tire I: thickness is 1.8mm, weight is 310g / m 2, purchased from Fadada Textile Company.

[0091] Glass fiber tire II: thickness 1.0mm, weight 110g / m 2 , purchased from Fadada Textile Company.

[0092] Base asphalt:

[0093] 70# asphalt: The needle penetration at 25°C is 72 0.1mm, the softening point is 52°C, purchased from Jingbo Company, the brand number is 70#.

[0094] 90# asphalt: The needle penetration at 25°C is 91 0.1mm, the softening point is 47°C, purchased from Gaofu Company, brand number 90#.

[0095] Polyolefin wax powder:

[0096] Polyethylene wax: viscosity of 450 mPa.s at 130°C, softening point of 108°C, number average molecular weight of 2800, purchased from Comino Company, brand number 206.

[0097] Oxidized polyethylene wax: viscosity is 250 mPa.s at 130°C, softening point is 114°C, number average molecular weight is 1300, purchased from Guangdong Qiaoxing Company, brand number 1085.

[0098] Polypropylene wax: viscosity is 360 mPa.s at 130°C, softening point is 118°C, number average molecular weight is 1600, purchased from Taili New Materials Co., Ltd., brand number 80H.

[0099] Thermoplastic Elastomers:

[0100] Thermoplastic elastomer I: butadiene-styrene-butadiene triblock copolymer, purchased from Baling Petrochemical Company, brand 813.

[0101] Thermoplastic elastomer II: butadiene-styrene diblock copolymer, purchased from Shandong Gaoshi, brand 473.

[0102] filler:

[0103] Heavy calcium I: The average particle size of the particles is 15 μm, purchased from Qixia Rongguan Company.

[0104] Heavy calcium II: The average particle size is 150 μm, purchased from Zhongshan Xiongding Company.

[0105] The areas of the glass fiber mats I and II in the following examples of the present invention are both 1m 2 .

[0106] The following Preparation Example A is used to illustrate the preparation of graphene oxide I.

[0107] Preparation Example A

[0108] S1: 200 mL of sulfuric acid, graphite (10.0 g) and potassium nitrate (10.0 g) were subjected to a first stirring reaction to obtain a mixture I;

[0109] The conditions of the first stirring reaction were: rotation speed of 200 rpm, temperature of 3°C, and time of 1 h;

[0110] S2: subjecting 10.0 g of potassium permanganate to a second stirring reaction with the mixture I to obtain an intermediate I;

[0111] The conditions of the second stirring reaction were: rotation speed of 300 rpm, temperature of 40°C, and time of 30 min;

[0112] S3: stirring the intermediate I, 400 mL of deionized water and 100 mL of hydrogen peroxide for reaction, filtering and washing the precipitate with hydrochloric acid for the first time, centrifuging and then washing the precipitate with deionized water for the second time until the pH of the solution after washing is 7.0, and drying the precipitate for the first time to obtain the graphene oxide I;

[0113] The stirring reaction conditions are: rotation speed of 300 rpm, temperature of 95° C., and time of 1 h.

[0114] The following Preparation Example B is used to illustrate the preparation of reduced graphene oxide.

[0115] Preparation Example B

[0116] The graphene oxide I obtained in the above-mentioned Preparation Example A was added with water to prepare a graphene oxide aqueous dispersion with a concentration of 50 mg / mL, and then 400 mL of the graphene oxide aqueous dispersion and 30 mL of hydrazine hydrate were heated (temperature of 90° C. for 2 h), and reduced graphene oxide was obtained after drying.

[0117] The following C series preparation examples and comparative preparation examples are used to illustrate the preparation of modified glass fiber tires.

[0118] Preparation Example C1

[0119] (i) stirring and mixing 400 mL of the graphene oxide aqueous dispersion and sodium tripolyphosphate to obtain an aqueous solution I;

[0120] (ii) The aqueous solution I, the raw glass fiber tire and hydrazine hydrate are heated and dried to obtain a modified glass fiber tire, which is named T1.

[0121] The recipe and process parameters of this preparation example are shown in Table 1.

[0122] Preparation Example C2

[0123] This preparation example is carried out by a method similar to that of Preparation Example C1, except that the formula and process parameters are different, and a modified glass fiber tire is obtained, named T2, as shown in Table 1.

[0124] Preparation Example C3

[0125] This preparation example is carried out by a method similar to that of Preparation Example C1, except that the formula and process parameters are different, and a modified glass fiber tire is obtained, named T3, as shown in Table 1.

[0126] Comparative Preparation Example C-D1

[0127] 20 g of reduced graphene oxide (prepared in the above-mentioned Preparation Example B) was evenly sprinkled on the surface of the glass fiber tire I to obtain a modified glass fiber tire, named DT1.

[0128] Comparative Preparation Example C-D2

[0129] This comparative preparation example is carried out using a method similar to that of Preparation Example C1, except that a glass fiber tire II of equal area is used to replace the glass fiber tire I in Preparation Example C1 to obtain a modified glass fiber tire, named DT2, as shown in Table 1.

[0130] Comparative Preparation Example C-D3

[0131] This comparative preparation example was carried out using a method similar to that of Preparation Example C1, except that the concentration of graphene oxide was adjusted from 50 mg / mL in Preparation Example C1 to 10 mg / mL while keeping the volume of the graphene oxide aqueous dispersion unchanged, to obtain a modified glass fiber tire, named DT3, as shown in Table 1.

[0132] Comparative Preparation Example C-D4

[0133] This comparative preparation example is carried out by a method similar to that of Preparation Example C1, except that an equal concentration of sodium carbonate is used to replace the sodium tripolyphosphate in Preparation Example C1 to obtain a modified glass fiber tire, named DT4, as shown in Table 1.

[0134] Comparative Preparation Example C-D5

[0135] This comparative preparation example was carried out using a method similar to that of Preparation Example C1, except that while controlling the volume of the graphene oxide aqueous dispersion to remain unchanged, the amount of sodium tripolyphosphate was changed so that the concentration of sodium tripolyphosphate in the aqueous solution I was adjusted from 2 mg / mL in Preparation Example C1 to 0.2 mg / mL, and a modified glass fiber tire was obtained, named DT5, as shown in Table 1.

[0136] Table 1

[0137]

[0138]

[0139] Table 1

[0140]

[0141] Different raw material formulations are used in the following examples of the present invention. Unless otherwise specified, all raw material amounts are parts by weight, and each part by weight represents 20 g.

[0142] Example 1

[0143] This example is used to illustrate that the composition for asphalt shingles of the present invention is prepared according to the formulation in Table 2 and the following method.

[0144] The method for preparing the asphalt shingle comprises the following steps:

[0145] (1) mixing base asphalt, polyolefin wax powder, thermoplastic elastomer and filler to obtain modified asphalt material;

[0146] The first mixing conditions were: rotation speed of 300 rpm, temperature of 180°C, and time of 2 h;

[0147] (2) impregnating the modified glass fiber mat with the modified asphalt material to obtain the asphalt shingle;

[0148] The conditions of the immersion treatment are as follows: temperature is 190°C and time is 2 minutes.

[0149] Example 2

[0150] This example is carried out in a similar manner to Example 1, except that the formula is different, as shown in Table 2.

[0151] Example 3

[0152] This example is carried out in a similar manner to Example 1, except that the formula is different, as shown in Table 2.

[0153] Example 4

[0154] This example is carried out in a similar manner to that of Example 1, except that an equal weight portion of thermoplastic elastomer II is used to replace the thermoplastic elastomer I in Example 1, and the rest is the same as that of Example 1, as shown in Table 2.

[0155] Example 5

[0156] This example is carried out in a similar manner to that of Example 1, except that an equal amount of heavy calcium II is used to replace the heavy calcium I in Example 1, and the rest is the same as in Example 1, as shown in Table 2.

[0157] Comparative Example 1

[0158] (1) 75 parts by weight of 70# asphalt, 5 parts by weight of polyethylene wax, 5 parts by weight of thermoplastic elastomer I, 10 parts by weight of heavy calcium I and 5 parts by weight of graphene are first mixed to obtain a modified asphalt material;

[0159] The first mixing conditions were: rotation speed of 300 rpm, temperature of 180°C, and time of 2 h;

[0160] (2) impregnating the glass fiber mat I with the modified asphalt material to obtain the asphalt shingle;

[0161] The conditions of the immersion treatment are as follows: temperature is 190°C and time is 2 minutes.

[0162] Comparative Example 2

[0163] (1) 75 parts by weight of 70# asphalt, 5 parts by weight of polyethylene wax, 5 parts by weight of thermoplastic elastomer I, 10 parts by weight of heavy calcium I and 5 parts by weight of reduced graphene oxide (prepared in Preparation B above) are first mixed to obtain a modified asphalt material;

[0164] The first mixing conditions were: rotation speed of 300 rpm, temperature of 180°C, and time of 2 h;

[0165] (2) impregnating the glass fiber mat I with the modified asphalt material to obtain the asphalt shingle;

[0166] The conditions of the immersion treatment are as follows: temperature is 190°C and time is 2 minutes.

[0167] Comparative Example 3

[0168] This comparative example adopts a method similar to that of Example 1, except that this comparative example uses a glass fiber mat I of equal area to replace the modified glass fiber mat T1 in Example 1.

[0169] Comparative Example 4

[0170] This comparative example adopts a method similar to that of Example 1, except that this comparative example adopts a modified glass fiber tire DT1 of equal area to replace the modified glass fiber tire T1 in Example 1.

[0171] Comparative Example 5

[0172] This comparative example adopts a method similar to that of Example 1, except that this comparative example adopts a modified glass fiber tire DT2 of equal area to replace the modified glass fiber tire T1 in Example 1.

[0173] Comparative Example 6

[0174] This comparative example adopts a method similar to that of Example 1, except that this comparative example adopts a modified glass fiber tire DT3 of equal area to replace the modified glass fiber tire T1 in Example 1.

[0175] Comparative Example 7

[0176] This comparative example adopts a method similar to that of Example 1, except that this comparative example adopts a modified glass fiber tire DT4 of equal area to replace the modified glass fiber tire T1 in Example 1.

[0177] Comparative Example 8

[0178] This comparative example adopts a method similar to that of Example 1, except that this comparative example adopts a modified glass fiber tire DT5 of equal area to replace the modified glass fiber tire T1 in Example 1.

[0179] Table 2

[0180]

[0181] Test Case

[0182] 1. The microscopic morphology of the glass fiber mat I in Preparation Example C1 of the present invention and the modified glass fiber mat T1 obtained in Preparation Example C1 were tested using a scanning electron microscope. The results are as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the modified glass fiber tire prepared by the method of the present invention has a denser three-dimensional network structure.

[0183] 2. The tear strength and electromagnetic shielding performance of the asphalt shingles prepared in the above examples were tested by the methods specified in GB / T 20474-2015 and GB / T 30142-2013, respectively. The results are shown in Table 3.

[0184] Table 3

[0185]

[0186]

[0187] It can be seen from the above results that the modified glass fiber tire prepared by the method of the present invention has a dense three-dimensional network structure and has good application prospects in asphalt shingles. The asphalt shingles prepared by the composition for asphalt shingles provided by the present invention have excellent tear resistance (tear strength>35N) and excellent electromagnetic shielding performance (electromagnetic shielding performance>35dB), and are particularly suitable for the field of building exterior walls with strict requirements on waterproofing and electromagnetic shielding.

[0188] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composition for asphalt shingles, characterized in that: The composition contains modified glass fiber tire and modified asphalt material; Relative to every 1m 2 The modified glass fiber tire, the content of the modified asphalt material is 1000-2000g; Based on the total weight of the modified asphalt material, the modified asphalt material contains 75wt%-85wt% of base asphalt, 3wt%-8wt% of polyolefin wax powder, 3wt%-8wt% of thermoplastic elastomer and 5wt%-15wt% of filler; The modified glass fiber tire is prepared by a method comprising the following steps: The aqueous solution I containing graphene oxide and polyphosphate, the raw glass fiber tire and the reducing agent are heated to obtain a modified glass fiber tire; The concentration of graphene oxide in the aqueous solution I is 30-80 mg / mL, and the concentration of polyphosphate is 1-3 mg / mL; The raw material glass fiber tire has a gram weight of ≥250g / m 2 ; Relative to every 1m 2 The raw glass fiber tire, the amount of the graphene oxide is 10-50g, and the amount of the reducing agent is 15-75mL; The thermoplastic elastomer is a butadiene-styrene-butadiene triblock copolymer and / or a butadiene-isoprene-butadiene triblock copolymer.

2. The composition according to claim 1, wherein The conditions of the heating treatment include: temperature of 80-120°C and time of 1-3h; And / or, the polyphosphate is at least one of ammonium polyphosphate, sodium tripolyphosphate, potassium tripolyphosphate, sodium polyphosphate and sodium hexametaphosphate; And / or, the reducing agent is hydrazine hydrate and / or vitamin C.

3. The composition according to claim 1 or 2, wherein The base asphalt has a needle penetration of 65-950.1 mm at 25°C and a softening point of 40-70°C; And / or, the polyolefin wax powder has a viscosity of 100-500 mPa.s at 130° C., a softening point of 100-120° C., and a number average molecular weight of 1200-3000.

4. The composition according to claim 1 or 2, wherein The polyolefin wax powder is selected from at least one of oxidized polyethylene wax, polyethylene wax, and polypropylene wax; And / or, the filler is selected from at least one of talc, heavy calcium, montmorillonite, kaolin and metakaolin; and the average particle size of the filler is 13-75 μm.

5. A method for preparing asphalt shingles, characterized in that: The method is carried out using the components in the composition according to any one of claims 1 to 4, comprising: (1) mixing base asphalt, polyolefin wax powder, thermoplastic elastomer and filler to obtain modified asphalt material; (2) The modified glass fiber base is impregnated with the modified asphalt material to obtain the asphalt shingle.

6. The method according to claim 5, wherein: In step (1), the first mixing conditions include: a rotation speed of 100-300 rpm, a temperature of 160-200° C., and a time of 1-3 h; And / or, in step (2), the conditions of the infiltration treatment include: temperature of 180-220° C. and time of 0.5-5 min.

7. Asphalt shingles prepared by the method of claim 5 or 6.

8. Use of the asphalt shingle according to claim 7 in waterproof construction.

Citation Information

Patent Citations

  • Colored asphalt shingle of electrically conductive snow melt

    CN206220376U

  • Heat-insulation flame-retardant asphalt shingle and preparation method thereof

    CN104358362A

  • Graphene doped ammonium polyphosphate flame retardant coated fabric and preparation method thereof

    CN107558181A

  • Colored glass fiber based asphalt shingle and preparation method thereof

    CN115572555A

  • Anti-haze photocatalyst composite building material aggregate and preparation method thereof

    CN117303789A